Alih Kode dan Campur Kode dalam Ceramah Ustazah Mumpuni Handayayekti pada Kanal Youtube Tv Umum - Meina Tri Kurniasih; Muhammad Burhanudin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is motivated by the symptoms of language selection in Ustazah Mumpuni Handayayekti, namely code switching and code mixing. The objectives of this study are 1) to describe the form of code switching in Ustazah Mumpuni Handayayekti's lecture, 2) to describe the factors causing code switching in Ustazah Mumpuni Handayayekti's lecture, 3) to describe the form of code mixing in Ustazah Mumpuni Handayayekti's lecture, 4) to describe the factors causing code mixing in Ustazah Mumpuni Handayayekti's lecture. This research is a qualitative descriptive research. The data source in this research is Ustazah Mumpuni Handayayekti's lecture video on Youtube. The data in this study are the speech of Ustazah Mumpuni Handayayekti which allegedly contains symptoms of code switching and code mixing. The data collection method in this research uses the listening method. As for the data collection technique, this research uses free listening and note-taking techniques. The data analysis method in this research uses the agih method. The results of this study show that there are several types of code switching and code mixing done by Ustazah Mumpuni Handayayekti. The forms of code switching found in this study are 1) internal code switching, 2) external code switching. While the form of code mix found in this study is code mix in the form of words, phrases, idioms, baster, and repetition. Factors causing code switching in Ustazah Mumpuni Handayayekti's lectures include 1) speakers, 2) speech partners, 3) to ease tension and inject humor, 4) changes in situation, and 5) changes in topic. While the factors causing code mix in Ustazah Mumpuni Handayayekti are 1) speakers, 2) limited word equivalents, 3) to generate a sense of humor, 4) to convey the message of cultural expression.